The Effect Of Prices And Facilities On Guest Stay At The Best Western Premier The Hive Hotel Jakarta - Fristi Bellia Bellia Annishia; Eko Prastiyo (Program Studi Hospitality dan Pariwisata, 2019)
ABSTRACTThe purpose of this research is to find out the effect of prices and facilities on the decision to stay at the Best Western Premier The Hive Hotel. The population in this study were guests who stayed at the Best Western Premier Hotel The Hive Jakarta. The number of samples successfully processed was 88 people, using simple random sampling. This study uses quantitative research design with multiple linear regression testing and previously performed several classical assumption tests. From the results of the study it was found that the value of the determinant coefficient or number R is equal to 0.259, then the relationship between the variable price and facilities to the variable decision of the stay is positive and strong. This is because Rsquare must be more or equal to 0.6 and close to number 1. For t count equal to 2.336 and for t table value from the result n-k-1 is 1.663. Thus it can be concluded that for the value of t count 2.336 <t table 1.663 then, the price variable has a significant effect on the decision to stay, then in this test the first hypothesis (H1) is accepted. In the Facility variable, the value of t count is 0.02 and the value of t table is 1.663, the facility does not affect the decision to stay. Suggestions that can be conveyed from this study include the price can be adjusted to the benefits that guests get when staying at a hotel, so the hotel can pay attention to the affordability of prices with the benefits obtained. In addition, the hotel should add facilities or have entertainment available in the lobby, so that guests who are waiting for the time to check in at the lobby do not feel bored and can make additional value for the hotel. Key words: facilities, guest, hotel, prices, decision to stay